Art to Life: The Preservation of Personhood - Emily Broman (The University of Alabama, 2022)
A sawmiller, veteran, and father from Pickens County, Alabama, Lester Potts was a practical man grounded in his faith and love for his family. But the handiness and helpfulness that had been the hallmark of his persona began to diminish with the onset of Alzheimer's disease at age 70. In the midst of his cognitive impairment and physical debilitation, Lester was losing elements of personal autonomy and sense of self. Because of his condition it was suggested to his family that he visit Caring Days, an adult daycare center specializing in artistic therapies. Lester was reluctant to do so and was only acquiesced into a visit under the impression he would be performing manual labor. And then, Lester Potts began to paint.